The Effects of Life Skills Training on Patients' Adaptation With Multiple Sclerosis - Mahnaz Seyedoshohadaee; Shima Parnian; Marjan Mardani; Hamid Haghani (Iran University of Medical Sciences, 2016)
Background: Multiple Sclerosis (MS) affects people's lives for a long time, therefore it is necessary to improve their quality of life by all means, including the most appropriate way of adaptation. The purpose of this study was to investigate the effect of life skills training on patients' adaptation with MS. Methods: This study is a quasi-experimental study with a sample size of 80 subjects who were selected with convenient sampling method. Patients were assigned in the experimental and control groups. The experimental group received four 1-hour sessions training of life skills within a month. The control group received routine cares. Patients in both groups completed Coping with Multiple Sclerosis Scale (CMSS) at the beginning and one month after the last training session. To compare the findings between two groups, independent T-Test was used and to compare pre- and post-intervention results, paired T-Test was used. To analyze the data, SPSS 21 was used. Results: Most respondents in both experimental and control groups (55% - 55.7%, respectively) were male. In the control group, the average age of respondents was 32.22 years and in the experimental group it was 33.02 years. There was no significant difference in coping with MS scores between experimental and control groups before life skills training (P > 0.05) but after training, both groups showed significant differences (P > 0.01). Conclusion: Our main study result suggests positive effects of using life skills training. Because the main objective of these trainings was preparing and helping patients to solve problems and difficulties encountered due to their diseases, thus, applying life skills training in care plan is recommended in these patients.